THE LEGALITY OF GRANTING LAND CONVERSION PERMITS IN FOOD ESTATE PROJECTS AS AN EFFORT TO REALIZE THE NATIONAL FOOD SECURITY PROGRAM - Indiyartono, Fahri; Trianjani, Suci; Gumilar, Egi Rivaldi; Amalia Nur Permata, Virna (Journal Social Sciences and Humanioran Review, 2024)
Currently the food estate project is one of the government's main focuses in implementing the national food security program. The development of a food estate has drawn pros and cons from the community. This raises public concerns that the construction of food estate projects could damage peatlands and protected forests. So this research aims to analyze the government's efforts to realize the national food security program through the construction of a food estate that utilizes peat land as an alternative planting medium as well as analyzing the legality of granting permits to convert peat land within protected forest areas as a follow-up to indications of crimes against the environment. In achieving the research objectives, the juridical-normative writing method was used. The results of this research provide information regarding the need for the government to work together to fulfill four important indicators for building large-scale food estates, which include: (1) agro-climate and soil suitability; (2) infrastructure feasibility; (3) technology; and social aspects of society. The legality of changing the function of peatland and the use of protected forests in food estate projects should be considered more carefully.